Farmhand (2018), volume 2 ebook Thorne in the flesh. - Guillory, Rob (Farmhand (2018), 2019)
Jedidiah Jenkins is a simple farmer. But his cash crop isn't corn or soy. Instead, he grows fast-healing, highly customizable human organs a miracle cure for all manner of ailments and injuries. Or they were, until his former patients began to transform into something not quite human. Now, these pour souls are coming to the Jenkins Farm searching for answers. But a dark figure lurks in their collective shadow one with sinister plans for Jedidiah, his family, and the world. Collects FARMHAND #6-10. Author: Rob Guillory. Illustrator: Rob Guillory, Taylor Wells . 2019 Rob Guillory.